NILAI KONSERVASI DALAM PEMBELAJARAN IPS DI SEKOLAH - Lestari, Puji (Program Studi IPS Universitas Negeri Semarang Kampus Sekaran, Gunungpati, Semarang, 2019)
Purpose this research to explore conservation values developed in the academic culture of the Semarang State University (UNNES), particularly in learning in Social Studies Education Study Programs, Faculty of Social Sciences as part of conservation-oriented campuses, and their relevance in social studies learning in school. The conservation value developed from the Spirit of Conservation, as a basis for the development of a scientific culture with a conservation perspective and the foundation of behavioral philophosis, as a character of students of the academic community in campus life. Examining the benefits of conservation values in for graduates who become social studies teachers in schools. Qualitative research with a descriptive analytical approach. Research subjects were lecturers, students, and alumni of Social Sciences Education, Faculty of Social Sciences. The analysis shows; first, the development of conservation-oriented learning, relevant and useful in the achievement of competencies (KI and KD) taught in schools so far. This conservation value is included in the formulation of character values written in the planning of learning, which is integrated in the implementation of learning, and evaluation of learning. Social studies learning materials in junior high school contain knowledge, attitudes and behaviors (psychomotor) conservation including nature conservation, cultural conservation, and conservation of values and morals. Secondly, the awareness of social studies teachers of Social Sciences Education Study Program alumni as conservation people, is useful as provisions and student capital to realize the pillars of natural, social and moral conservation in their habitus. This study recommends the importance of more concrete and clear structuring of learning subjects in the Social Studies Study Program which can later provide students with knowledge about conservation values that must be implemented in daily life as an academic culture of conservation-oriented universities. Riset ini bertujuan untuk mengeksplorasi tentang nilai-nilai konservasi yang dikembangkan dalam budaya akademik Universitas Negeri Semarang (UNNES), khususnya dalam pembelajaran pada Program Studi (Prodi) Pendidikan IPS, Fakultas Ilmu Sosial sebagai bagian dari kampus berwawasan konservasi, dan relevansinya dalam pembelajaran IPS di sekolah. Nilai konservasi yang dikembangkan dari Spirit Konservasi, sebagai dasar pengembangan budaya keilmuan berwawasan konservasi dan landasan filofosis perilaku, sebagai karakter mahasiswa sivitas akademik dalam kehidupan kampus. Menelisik kemanfaatan nilai-nilai konservasi dalam bagi lulusan yang menjadi guru IPS di sekolah. Penelitian kualitatif dengan pendekatan deskriptif analitis. Subjek penelitian yakni dosen, mahasiswa, dan alumni Pendidikan IPS, Fakultas Ilmu Sosial. Hasil analisis menunjukkan; pertama, pengembangan pembelajaran berwawasan konservasi, relevan dan bermanfaat dalam capaian kompetensi (KI dan KD) yang diajarkan di sekolah selama ini. Nilai konservasi ini masuk pada rumusan nilainilai karakter yang ditulis dalam perencanaan pembelajaran, yang terintegrasi pada pelaksanaan pembelajaran, dan evaluasi pembelajaran. Materi pembelajaran IPS SMP mengandung pengetahuan, sikap dan perilaku (psikomotor) konservasi meliputi konservasi alam, konservasi budaya, dan konservasi nilai dan moral. Kedua, kesadaran guru IPS alumni Program Studi Pendidikan IPS sebagai insan konservasi, bermanfaat sebagai bekal dan modal mahasiswa mewujudkan pilar konservasi alam, sosial dan moral dalam habitus mereka. Penelitian ini merekomendasi pentingnya penataan lebih konkrit dan jelas terhadap pembelajaran mata kuliah di Program Studi Pendidikan IPS yang nantinya dapat memberi pengetahuan kepada mahasiswa tentang nilai-nilai konservasi yang harus diimplementasikan dalam kehidupan sehari-hari sebagai budaya akademik universitas berwawasan konservasi.